The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/hed.23626
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent chemoradiotherapy compared with surgery and adjuvant radiotherapy for oral cavity squamous cell carcinoma

Abstract: Treatment by surgery + adjuvant RT for advanced oral cavity SCC resulted in better disease control than treatment with CRT. This supports traditional surgical treatment algorithms for oral cavity cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 15 publications
6
44
0
2
Order By: Relevance
“…The reported 5-year disease-specific survival was 68% in the surgery arm versus 12% in the chemoradiation arm (p = 0.038) [7] . Similar conclusions have been reported in retrospective studies by Gore et al [8] .…”
Section: Surgery As the Treatment Option In Oral Cancersupporting
confidence: 81%
“…The reported 5-year disease-specific survival was 68% in the surgery arm versus 12% in the chemoradiation arm (p = 0.038) [7] . Similar conclusions have been reported in retrospective studies by Gore et al [8] .…”
Section: Surgery As the Treatment Option In Oral Cancersupporting
confidence: 81%
“…Usually, surgical treatment is preferred in the initial oral cancer, and the cases of progressed oral cancer with cervical lymph node metastasis can be provided with surgical treatment along with chemotherapy and radiation therapy [22]. Previous studies reported that overall survival and disease-specific survival was significantly higher in the surgically treated group compared with no surgery group in oral cavity squamous cell carcinoma [2325]. Surgery and/or radiation therapy provides disease-specific survival benefit as compared with no therapy within the head and neck region [26].…”
Section: Discussionmentioning
confidence: 99%
“…A main meta-analysis showed only a small significant survival benefit in favour of chemotherapy, so the routine use of chemotherapy is debatable [31]. Studies about oral cancer also showed that combination therapy with chemotherapy after surgical treatment is not significantly better than those who received only surgical treatment or surgery plus radiotherapy [23]. Results from this study suggest that surgery combined with chemotherapy or concurrent chemoradiotherapy may not be significantly associated with overall survival of oral cancer after adjusting for the effect of gender, age, BMI, occupation, origin, education, drinking, smoking, family history, clinical stage, pathological grading.…”
Section: Discussionmentioning
confidence: 99%
“…The primary choice of treatment will normally be surgery, with or without adjuvant radiotherapy [1]. If the functional consequences of surgery would reduce the quality of life to an unacceptable extent, the tumour is considered ‘functionally inoperable’ [2], and organ-sparing chemoradiation treatment will provide a better alternative.…”
Section: Introductionmentioning
confidence: 99%